Prevent Stunting Early: Implementing Nutrition Education through a Shared Breakfast Program in Elementary Schools - Nurlela Petra Saragih; Almina Rospitaria Tarigan; Eka Isranil Laily; Elfrida Nainggolan; Ruth Sarah Julfrida Saragih; Dewi Sartika Munthe (CV. AFDIFAL MAJU BERKAH, 2025)
Stunting (chronic malnutrition) remains a serious public health challenge in Indonesia, with a prevalence of 21.6% (2022) above the WHO threshold (20%). While interventions are intensive during the First 1000 Days of Life, management during the school-age period (the second golden phase) is often neglected. This study aims to measure the effectiveness of nutritional education intervention and hands-on practice through a Shared Breakfast Program in Elementary Schools (SD) in improving nutritional knowledge and stunting prevention. This community service activity used a simple pre-test and post-test design with a participatory education method on 49 students from grades 1 to 3 at Talang Bukit Hutabayu State Elementary School. The material focused on the dangers of stunting, the concept of Balanced Nutrition (Isi Piringku or My Plate Content), and the importance of breakfast. The results showed a significant increase in students' knowledge levels, with average score improvements ranging from 23.6% to 33.5% between the pre-test and post-test. The greatest improvement occurred in Grade 1 students. The Shared Breakfast Program proved effective as a live laboratory that transformed abstract nutritional concepts into tangible practice. The intervention not only enhanced nutritional literacy but also built awareness of the link between a healthy breakfast and learning concentration. It is recommended that a comprehensive nutrition program, supported by continuous teacher training and active parental involvement, be integrated into the school curriculum to ensure the sustainability of healthy behavior changes